Recent Advances in Our Knowledge of Baculovirus Molecular Biology and Its Relevance for the Registration of Baculovirus-Based Products for Insect Pest Population Control - Lapointe, Renée; Thumbi, David; Lucarotti, Christopher J. (IntechOpen, 2012)
None